Secondary DNA Barcodes (CAM, GAPDH, GS, and RpB2) to Characterize Species Complexes and Strengthen the Powdery Mildew Phylogeny - Bradshaw, Michael J.; Guan, Guan-Xiu; Nokes, Liam; Braun, Uwe; Liu, Shu-Yan; Pfister, Donald H. (Frontiers in Ecology and Evolution, 2022)
Powdery mildews are a group of economically and ecologically important plant pathogens. In the past 25 years the use of rDNA in the powdery mildews has led to major taxonomic revisions. However, the broad scale use of rDNA has also demonstrated multiple species complexes that cannot be differentiated based on ITS+LSU data alone. Currently, there are only two powdery mildew taxonomic studies that took a multi-locus approach to resolve a species complex. In the present study, we introduce primers to sequence four additional regions (CAM, GAPDH, GS and RPB2) that have the potential to improve support values in both broad and fine scale phylogenetic analyses. The primers were applied to a broad set of powdery mildew genera in China and the USA, and phylogenetic analyses included some of the common complexes. In taxa with nearly identical ITS sequences the analyses revealed a great amount of diversity. In total 154 non rDNA sequences from 11 different powdery mildew genera were deposited in NCBI’s GenBank, laying the foundation for secondary barcode databases for powdery mildews. The combined and single loci phylogenetic trees constructed generally followed the previously defined species/genus concepts for the powdery mildews. Future research can use these primers to conduct in depth phylogenetic, and taxonomic studies to elucidate the evolutionary relationships of species and genera within the powdery mildews.